ECOLOGICAL PROBLEMS AND THREATS TO HUMAN HEALTH: HISTORICAL AND MODERN ANALYSIS - Shodiyeva Sarvinoz Shuhrat kizi (Western European Studies, 2025)
This article presents specific figures and examples of atmospheric pollution, the spread of toxic gases and the disruption of the ecological balance. It is emphasized that this problem is relevant not only for Uzbekistan, but for all of humanity. It is shown that modern industry and technologies operate contrary to the principles of environmental safety. This leads to pollution of environments such as air, water, and soil.
Keywords: Modern environmental problems; History of nature conservation; Ancient nature reserve traditions in Central Asia